Efektivitas Penerapan Pusaka Kemenag Dalam Meningkatkan Kedisiplinan Pegawai di Madrasah Aliyah Negeri 2 Kolaka - Manda Sari; Achmad Lamo Said; Ahmad Farouq Mulku Zahari; Firdaus Firdaus (Universitas Warmadewa, 2025)
This study aims to assess the effectiveness of the implementation of the Absensi Pusaka Kemenag (Online Attendance) system in enhancing the discipline of Civil Servants at MAN 2 Kolaka. The methodology employed is qualitative with a descriptive approach. The findings indicate that the implementation of the Absensi Pusaka Kemenag has been successful. The first indicator in the Tangkilisan theory demonstrates that the target for improving discipline has been achieved. Based on the attendance recapitulation, there has been an increase in employee attendance from 89.75% using fingerprint attendance to 95.37% following the implementation of the Absensi Pusaka system. Furthermore, employees have shown a good ability to adapt to the new system, attributed to effective socialization efforts. Additionally, job satisfaction has improved, as evidenced by higher work morale among employees. The responsibility of employees in utilizing the attendance application has also been effectively fulfilled, supported by the user-friendly nature of the application and the provision of assistance in resolving attendance-related issues. Consequently, the implementation of the Absensi Pusaka Kemenag contributes positively to the discipline and work enthusiasm of employees at MAN 2 Kolaka.